Strengthening School Branding Through Digital Technology - Diana, Eka Diana; Ariska, Lulus; Mufidah, Imroatun Dilla; Hasanah, Ruhanatul; Dewi, Nur Putri; Wulandari, Deli (Indo-MathEdu Intellectuals Journal, 2025)
This ever-evolving digital age, educational institutions face challenges in maintaining their existence and increasing their competitiveness. The purpose of this study is to analyse strategies for strengthening school branding by optimising digital platforms, including Instagram, YouTube, and the school website, at Madrasah Aliyah Darul Ulum Paiton. This study uses a qualitative paradigm with a case study approach. The survey is conducted at Madrasah Aliyah Darul Ulum Paiton, based on considerations that facilitate the collection of research information and data. The data sources for this study were primary and secondary. The data collection techniques in this study were participant observation and in-depth interviews. The data analysis techniques consisted of data reduction, data presentation, and conclusion drawing. The results showed that Madrasah Aliyah Darul Ulum Paiton strategically used digital platforms such as Instagram, YouTube, and the school website to build a positive image in the community, increase student participation in creative content, and establish interactive two-way communication with the public. The active involvement of the principal, teachers, students, and public relations team is key to the success of the digital branding strategy. The optimisation of digital technology significantly improves the school's image, attractiveness, and public trust, and fosters a strong, sustainable digital identity.